2018
DOI: 10.1111/jfb.13495
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic copepods affect morphospace and diet of larvae of a temperate reef fish

Abstract: The effects of ectoparasites on larvae of the clingfish Gobiesox marmoratus were evaluated at the dietary and morphometric levels. The larvae and ectoparasites were collected by nearshore plankton samplings during October, November and December 2013 off El Quisco Bay, central Chile. The standardized abundance of total larvae and those ectoparasitized larvae (PL) was positively related and high parasite prevalence was found throughout the sampling period (up to 38%). Geometric morphometrics analyses indicate ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Studies of copepods parasitizing fish larvae around the world are scarce. However, a few studies have reported parasitic larvae of the family Pennellidae on larval fish belonging to different families 4,5,7 . Our study adds more data to the record of such ectoparasites; this work documented ectoparasitic pennellid larvae (Trifur sp.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of copepods parasitizing fish larvae around the world are scarce. However, a few studies have reported parasitic larvae of the family Pennellidae on larval fish belonging to different families 4,5,7 . Our study adds more data to the record of such ectoparasites; this work documented ectoparasitic pennellid larvae (Trifur sp.)…”
Section: Discussionmentioning
confidence: 99%
“…Parasites in fish larvae could have detrimental impacts on the nutritional and immune response as well as mechanic effects can be caused by parasites via their own body weight 11 . All of these levels could affect the larval growth prior to settlement in fish species 7 . In our study, positive correlations between parasite size and larval fish size were recorded in A. crinitus, G. marmoratus, and Myxodes sp., reflecting that, at least in northern latitudes of the HCS, ectoparasites infest the larval fish species early in the planktonic larval stage, and both grow together until the larval copepod detaches and looks for its next host, suggesting that there are no lethal or detrimental effects on fish larvae survival.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to notice the difference in the diet of larval G. marmoratus with the sympatric clingfish Sicyases sanguineus Müller & Troschel 1843, even when both species have similar body shape prior to 7 mm L N (Bernal‐Durán et al ., ). While small larval G. marmoratus ingest larval gastropods, invertebrate eggs (this study) and cirriped nauplii (Jahnsen‐Guzmán et al ., ), larvae of S. sanguineus ate mostly copepod nauplii and eggs (Bernal‐Durán & Landaeta, ). This suggests resource partitioning between both sympatric species during their pelagic stages.…”
Section: Discussionmentioning
confidence: 99%
“…Only preflexion larvae were selected to avoid or reduce confounding effects of the ontogenetic variability in the diet described in other clingfish species during larval development (Bernal‐Durán & Landaeta, ). Larvae with ectoparasites were not considered in this study because they may affect larval diet (Jahnsen‐Guzmán et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation